Analysis of Junior High School Students’ Mathematical Reasoning Ability on Two Variables Linear Equation System Material - Permatasari, Sri Nurwahyuni; Hendriana, Heris; Yuliani, Anik (IKIP Siliwangi, 2025)
Mathematical reasoning ability is one of the essential mathematical abilities that students must master well. This research aims to analyze the mathematical reasoning abilities of junior high school students on two variables linear equations system material. The research was conducted at SMP Negeri 69 Bandung involving grade eighth students as research subjects. The samples taken were 21 students. This research uses a qualitative descriptive approach. Data collection was carried out through documentation of test instruments in the form of mathematical reasoning ability tests. The analysis results show that the percentage of student errors varies for each indicator of reasoning ability. In detail, the first and second indicators show a very low error percentage, namely 11% and 27%. However, in the third, fourth, and fifth indicators, the percentage of errors increased significantly, by 67%, 69%, and 56% respectively, which is categorized as moderate and low. The sixth indicator shows the highest percentage of errors, which is 89%, which is in the high category. Overall, the average percentage of student errors is 53.17%, which can generally be categorized as very low. These findings indicate a variation in students' mathematical reasoning abilities in two variables linear equations system material. In addition, this study is also expected to contribute to identifying the types of errors commonly made by students and their implications for improving the mathematics learning process.